GAJI PENDIDIK DALAM TEORI-TEORI PENDIDIK - Siti Noer Farida Laila (Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2015)
Viewing educator as a "profession" means considering not only the compliance of elements and scientific procedures but also the fulfillment of salaries for professional staff. Payroll practices of educators had been institutionalized in medieval Islamic educational system, although the institutionalization process had invited controversy among scholars. Along with the institutionalization of the payroll practices of educators, educational theories evolved toward a discussion of issues of the competences of educators who make teaching activities as a "profession". The historical experience of Muslims can give us a lesson for resolving the problems of professionalism of educators today.Kata kunci: Teori, Gaji, Pendidik